Design, Analysis and Optimization of Crane Hook Model Din 15401 - Lenin Rakesh, N.; Kumar Mishra, Nikhil; Kumar, Piyush (International Journal of Psychosocial Rehabilitation, 2019)
Crane hooks are highly liable components and are always subjected to failure due to the accumulation of a large amount of stress, which can eventually lead to their failure. In this paper, the design of the hook is done by the analytical method, and the design is done for the different materials, like forged steel and high-tensile steel. After the analytical method, design and modeling of hooks are done in modeling software (pro-E). The modeling is done using the design calculation. From the modeling, the analysis of the hook is done in FEA software (ANSYS).